Causality in the Sciences 2011
DOI: 10.1093/acprof:oso/9780199574131.003.0035
|View full text |Cite
|
Sign up to set email alerts
|

Predicting ‘It will work for us’: (Way) beyond statistics

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 2 publications
0
25
0
Order By: Relevance
“…8. Cartwright (2011) is another proponent of the view that successful extrapolation requires evidence that goes beyond statistical studies.…”
Section: Resultsmentioning
confidence: 99%
“…8. Cartwright (2011) is another proponent of the view that successful extrapolation requires evidence that goes beyond statistical studies.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, in Cartwright (2011;, Cartwright, and Hardie (2013) and Rol and Cartwright (2012) it has been suggested that the best way to overcome this problem is to focus on the details of the population in which the intervention is intended to be implemented. Methods for hunting causes only provide information regarding a policy that worked somewhere.…”
Section: Invariance In Policy Implementation: the Nancy Cartwright's mentioning
confidence: 99%
“…Organizational researchers would benefit from understanding how incorporating or shifting toward Bayesian methods will lead to different assumptions, and how Bayesian probability and methods can facilitate a capable shift when moving research findings from specific contexts to other domains-perhaps through practice (e.g., Verran, 2001). For guidance on developing "evidence for use," a welldeveloped framework is by Cartwright (2006Cartwright ( , 2007Cartwright ( , 2010.…”
Section: Empirical Management Research That Features Specific Types Omentioning
confidence: 99%